Higher education funding and access in international perspective - Riddell, Sheila, 1953-; Minty, Sarah; Weedon, Elisabet; Whittaker, Susan (Bingley, U.K. : Emerald Publishing Limited, 2018)
This book explores the way in which the pressures of globalisation are shaping higher education funding and access across the world. Higher education is seen as a way of developing human capital and building knowledge economies, but major debates continue about who should attend university; how the costs of higher education should be distributed between the individual student and the state; how students from non-traditional backgrounds can be helped to succeed in higher education; and the intended and unintended consequences of widening access initiatives.Globalisation is not a uni-directional force, but is accompanied by movements to reinforce the local and the regional, often driven by fears of loss of identity. Universities across the world have become more powerful and autonomous from the state, but at the same time students as consumers of education have an increasingly powerful voice. They frequently find themselves in opposition to the business model which infuses higher education systems and student protests have had a strong influence on policy development. This book explores the way in which the twin pressures of globalisation and localisation play out in higher education across the developed world, often reflected in more specific debates on fees regimes, access and culture.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Universities and colleges -- Finance; Education, Higher; Education -- Higher; Higher & further education, tertiary education